Three-Dimensional Assessment of Pharyngeal Volume on Computed Tomography Scans: Applications to Anesthesiology and Endoscopy. Issue 3 (May 2020) - Gibelli, Daniele; Cellina, Michaela; Gibelli, Stefano; Oliva, Antonio Giancarlo; Termine, Giovanni; Sforza, Chiarella
Abstract : Abstract: Pharyngeal volume is important in anesthesiology for correctly assessing intubation procedures. However, most of studies are based on patients in upright position and do not assess possible relationships between pharyngeal volume and cranial size. This study aims at measuring pharyngeal volume in CT-scans and to assess possible statistically significant differences according to sex. Eighty healthy subjects (40 males and 40 females) aged between 21 and 86 years were retrospectively chosen from a hospital database of maxillofacial CT-scans; 3D segmentation was performed separately for naso-, oro- and laryngopharyngeal portion through ITK-SNAP software, and their volume was calculated. Three cranial measurements were obtained: distance between anterior and posterior nasal spine, upper facial height (nasion-prosthion) and biorbital breadth (ectoconchion-ectoconchion distance). The effect of sex on volume for each pharyngeal portion was assessed through one-way ANCOVA test using each of the 3 cranial measurements as covariate ( P < 0.05). On average, the volume of nasopharynx, oropharynx and laryngopharynx was 7.2 ± 2.7 cm 3, 7.5 ± 4.2 cm 3, 3.5 ± 2.2 cm 3 respectively in males, and 6.4 ± 2.9 cm 3, 5.2 ± 2.1 cm 3, 3.0 ± 1.8 cm 3 in females. Statistically significant differences according to sex were found only for oropharyngeal volume, independently from cranial measurements ( P < 0.05). This study provides data concerning volume of pharyngeal air space in supine subjects: these reference standards can be useful for anaesthesiologic procedures. Abstract : Supplemental Digital Content is available in the text